Impact of past obstetric history and cervical excision on preterm birth rate - Collins, Anna; Motiwale, Tanushree; Barney, Olivia; Dudbridge, Frank; McParland, Penelope C.; Moss, Esther L. (Acta obstetricia et gynecologica Scandinavica, 2021)
Introduction To determine the impact on preterm birth (PTB) of a history of large loop excision of the transformation zone (LLETZ)‐alone compared with a history of previous preterm birth‐alone (PPTB) or a history of both (LLETZ+PPTB). Secondary analyses were performed to evaluate the impact of antenatal interventions, depth of cervical excision, and patient risk factors on PTB rate in each cohort. Material and methods A retrospective observational cohort study of women referred to a tertiary Antenatal Prematurity Prevention Clinic with a history of LLETZ, PPTB, or LLETZ+PPTB. Information was collated from routinely collected clinical data on patient demographics, previous obstetric history, LLETZ dimensions, antenatal investigations/interventions, and gestation at delivery. Results A total of 1231 women with singleton pregnancies were included, 543 with history of LLETZ‐alone, 607 with a history of PPTB‐alone and 81 with a history of LLETZ+PPTB. PTB rates were 8.8% in the LLETZ‐alone group, which mirrored the PTB rate in the local background obstetric population (8.9%) compared with 28.7% in the PPTB‐alone and 37.0% in the LLETZ+PPTB cohorts. PTB rates were higher in LLETZ cohorts treated with antenatal intervention (cervical cerclage or progesterone pessary) and there was no evidence of an effect of intervention on risk of PTB in post‐excision patients with identified shortened mid‐trimester cervical length. Logistic regression modeling identified PPTB as a strong predictor of recurrent PTB. Excision depth was correlated with gestation at delivery in the LLETZ‐alone group (r = −0.183, p < 0.01) although this only reached statistical significance at depths of 20 mm or more (odds ratio [OR] 3.40, 95% CI 1.04–1.11, p = 0.04). Depth of excision was not correlated with delivery gestation in the LLETZ+PPTB group (r = −0.031, p = 0.82). Conclusions PPTB has a greater impact on subsequent PTB risk compared with depth of cervical excisional treatment. The value and nature of antenatal interventions should be investigated in the post‐excision population. A retrospective observational cohort study to determine the impact on preterm birth (PTB) of a history of LLETZ‐alone compared with a history of previous preterm birth alone or a history of both LLETZ +PPTB was performed. PTB rates in the LLETZ‐alone group mirrored the PTB rate in the local background obstetric population compared with higher rates in the PPTB‐alone and the LLETZ+PPTB cohorts. Preterm birth rates were higher in LLETZ cohorts treated with antenatal intervention (cervical cerclage or progesterone pessary) and there was no evidence of an effect of intervention on risk of preterm birth in post‐excision patients with identified shortened mid‐trimester cervical length. PPTB has a greater impact on subsequent PTB risk compared with depth of cervical excisional treatment. The value and nature of antenatal interventions should be investigated in the post‐excision population.